Observational Evidence of Negative Leader Reactivation Processes Following a Negative Return Stroke in Lightning Discharges - Huaifei Chen; Weijiang Chen; Yu Wang; Nianwen Xiang; Kejie Li; Zhong Fu; Hengxin He; Lilang Xiao (Geophysical Research Letters)
Abstract High‐time‐resolved mapping results of two rare reactivation processes following a negative return stroke are discovered and analyzed. The reactivation processes can be roughly divided into two different stages. At first, positive discharges occurred for tens of milliseconds in a limited space near a decayed negative leader channel. The discharges produced no detectable electric field change. Then, negative discharges started and propagated along the decayed downward negative leader channels at a speed exceeding 106 m/s for a few microseconds and produced negative electric field changes. The analysis reveals that the reactivation processes are physically distinct from recoil leaders and side discharges regarding propagation behaviors, electromagnetic characteristics, and time scales. The possible mechanisms of the processes are discussed. The observation suggests that the reactivation processes of the negative leaders may lead to subsequent return strokes.